Влияние скорости нагрева в процессе искро-плазменного спекания на кинетику уплотнения, структурообразование и свойства материалов системы Fe–Ti–C–(B) - Присташ, Н.С.; Сизоненко, О.Н.; Зайченко, А.Д. (Вісник Українського матеріалознавчого товариства, 2016)
Experimental data about impact of heating rate in range from 10 up to 20 °C/s under spark plasma sintering on grain size, structure and mechanical properties of Fe–Ti–C–(B) carbide steels system is given. It was established, that increasing heating rate up to 20 °C/s in consolidation mode with holding temperature of 1100 °􀉋 during 180 seconds leads to decrease of mean iron grain size in material structure from ~3.5 to ~2 􀈝m and allows to obtain Fe–Ti–C–(B) carbide steels system with hardness of 70 HRC and wear-resistance seven times higher than of tungsten-containing HSS M2 steel.